Market competition and the use of performance measures in Malaysia manufacturing companies. - Ong, Tze San; Teh, Boon Heng (2008)
This paper reports the results of an empirical study into the use of multiple performance measures in manufacturing companies in Malaysia. More specifically, it investigates how a performance measurement system is linked with the intensity of market competition. To test this relationship, data were collected from 77 Malaysian manufacturing organizations, across a wide range of organizational size and sub-sectors. Analyses included the use of descriptive, chi-square tests and one-way ANOVA between and within groups. The findings indicate that greater emphasis on multiple performance measures is associated with businesses facing intense competition.